Heat Transfer Performance of Titanium Oxide in Ethylene Glycol Based Nanofluids under Transition Flow - Khamisah, Abdul Hamid; Azmi, W. H.; R., Mamat; N. A., Usri (Trans Tech Publications, Switzerland, 2014)

(untitled)
The needs to improve the efficiency of coolants undeniably become one of the concerns in cooling systems technologies nowadays. Nanofluid as coolant is invented and studied where it can provide better option for users due to augmentation in properties. This study provides experimental investigation on Titanium Oxide dispersed in water and ethylene glycol mixture under transition region with Reynolds number range of 2000 < Re <10000. Three volume concentrations are used which are 0.5 %, 1.0 % and 1.5 % for heat transfer experimental investigation under working temperature of 30 °C at constant heat flux of 600 W. The Nusselt number of the nanofluid increase with the increasing of Reynolds number at 1.5 % concentration, slightly higher than based fluid. The finding on the heat transfer coefficient shows enhancement of 2.1 % achieved by Titanium Oxide nanofluid at 1.5 % volume concentration. For 0.5 % and 1.0 % concentration, no enhancement of heat transfer achieved for the fluid flow under transition region at temperature of 30 °C.